Is mammalian chromosomal evolution driven by regions of genome fragility? - Aurora Ruiz‐Herrera; José Castresana; Terence J. Robinson (2006)
Abstract Background A fundamental question in comparative genomics concerns the identification of mechanisms that underpin chromosomal change. In an attempt to shed light on the dynamics of mammalian genome evolution, we analyzed the distribution of syntenic blocks, evolutionary breakpoint regions, and evolutionary breakpoints taken from public databases available for seven eutherian species (mouse, rat, cattle, dog, pig, cat, and horse) and the chicken, and examined these for correspondence with human fragile sites and tandem repeats. Results Our results confirm previous investigations that showed the presence of chromosomal regions in the human genome that have been repeatedly used as illustrated by a high breakpoint accumulation in certain chromosomes and chromosomal bands. We show, however, that there is a striking correspondence between fragile site location, the positions of evolutionary breakpoints, and the distribution of tandem repeats throughout the human genome, which similarly reflect a non-uniform pattern of occurrence. Conclusion These observations provide further evidence that certain chromosomal regions in the human genome have been repeatedly used in the evolutionary process. As a consequence, the genome is a composite of fragile regions prone to reorganization that have been conserved in different lineages, and genomic tracts that do not exhibit the same levels of evolutionary plasticity.